2014
DOI: 10.1530/rep-13-0464
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of hyaluronan synthesis in ovarian follicle growth in rats

Abstract: Most of the previous studies on ovarian hyaluronan (HA) have focused on mature antral follicles or corpora lutea, but scarcely on small preantral follicles. Moreover, the origin of follicular HA is unknown. To clarify the localization of HA and its synthases in small growing follicles, involvement of HA in follicle growth, and gonadotropin regulation of HA synthase (Has) gene expression, in this study, perinatal, immature, and adult ovaries of Wistar-Imamichi rats were examined histologically and biochemically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 33 publications
(46 reference statements)
1
14
0
Order By: Relevance
“…In particular, we focused on hyaluronan as its metabolism plays a central role in follicular development (Figure ). It is synthetized in granulosa cells and secreted into the follicular fluid where it maintains folliculogenesis and prevents oocyte degeneration . Hyaluronan degradation may be associated with follicular atresia .…”
Section: Extra‐cerebral Involvementmentioning
confidence: 99%
“…In particular, we focused on hyaluronan as its metabolism plays a central role in follicular development (Figure ). It is synthetized in granulosa cells and secreted into the follicular fluid where it maintains folliculogenesis and prevents oocyte degeneration . Hyaluronan degradation may be associated with follicular atresia .…”
Section: Extra‐cerebral Involvementmentioning
confidence: 99%
“…In the ovary, HA inhibits human follicular granulosa cell (GC) apoptosis 3 , consistent with its function in porcine GC (pGC) apoptosis 4 . Inhibition of ovarian HA synthesis with chemicals, such as deoxynivalenol, induces follicular atresia, and addition of Streptomyces hyaluronidase, which specifically degrades HA, induces the arrest of follicle growth in an in vitro culture system 5 . Likewise, the anti-apoptotic role of HA is evident in other cells, such as skin fibroblasts 6 and smooth muscle cells 7 .…”
mentioning
confidence: 99%
“…Knockout studies in mice showed that Has2 −/− embryos lack HA, resulting in embryonic lethality during mid-gestation 10 11 . HAS2 has a close relationship with ovary development and function, and is predominantly located in the GC layers of rat and sheep ovaries 5 12 . Knockdown of CCAAT-enhancer-binding protein CEBβ decreases the HAS2 mRNA level and results in the arrest of pGCs at S phase of the cell cycle, indicating that HAS2 plays an important role in GC function 13 .…”
mentioning
confidence: 99%
“…In cow, but also in horse in particular the expression of HAS2 is strongly induced by gonadotropins in GC of pre-ovulatory follicles [ 39 , 40 ]. In the rat Has1 and Has2 transcripts are expressed in cells of the theca and granulosa, whereas HA molecules are predominantly localized in the extracellular matrix of the theca layer, within the follicular fluid, but also the zona pellucida of large antral follicles [ 41 ]. Interestingly, also B3GALT2 transcripts, encoding the membrane-bound glycoprotein enzyme “UDP-Gal:betaGlcNAc beta 1,3-galactosyltransferase”, which is involved in the modification of cell surface molecules and thus cell-cell interactions were strongly up-regulated in GC of the HS group.…”
Section: Discussionmentioning
confidence: 99%